Between shades of gray ebook - Sepetys, Ruta (2011)
The inspiration for the major motion picture Ashes in the Snow ! "Few books are beautifully written, fewer still are important; this novel is both." — The Washington Post From  New York Times  and international bestseller and Carnegie Medal winner Ruta Sepetys, author of  Salt to the Sea , comes a story of loss and of fear — and ultimately, of survival. A  New York Times  notable book An international bestseller A Carnegie Medal nominee A William C. Morris Award finalist A Golden Kite Award winner Fifteen-year-old Lina is a Lithuanian girl living an ordinary life — until Soviet officers invade her home and tear her family apart. Separated from her father and forced onto a crowded train, Lina, her mother, and her young brother make their way to a Siberian work camp, where they are forced to fight for their lives. Lina finds solace in her art, documenting these events by drawing. Risking everything, she imbeds clues in her drawings of their location and secretly passes them along, hoping her drawings will make their way to her father's prison camp. But will strength, love, and hope be enough for Lina and her family to survive? A moving and haunting novel perfect for readers of  The Book Thief . Praise for  Between Shades of Gray : "Superlative. A hefty emotional punch." — The New York Times Book Review "Heart-wrenching . . . an eye-opening reimagination of a very real tragedy written with grace and heart." — The Los Angeles Times "At once a suspenseful, drama-packed survival story, a romance, and an intricately researched work of historial fiction." — The Wall Street Journal * "Beautifully written and deeply felt . . . An important book that deserves the widest possible readership." — Booklist , starred review “A superlative first novel. A hefty emotional punch.”— The New York Times Book Review “A brilliant story of love and survival.”—Laurie Halse Anderson, bestselling author of Speak and Wintergirls  * “Beautifully written and deeply felt…an important book that deserves the widest possible readership.”— Booklist , Starred Review